Factors influencing midwives' professional belongingness in northwest Ethiopia: Multicenter study - Eshetu Tsegaye Fenta; Wubedle Zelalem Temesgan; Mengstu Melkamu Asaye (Elsevier, 2023)
Background: Professional belonging is an individual's engagement in their profession and where they see themselves in that profession. Midwives who have strong sense of belonging can provide compassionate care to pregnant women, newborns and families throughout their lives. The generation of evidence on sense of midwives professional belongingness is a critical step for maternal and neonatal mortality reduction. However, there is a lack of evidence about professional belongingness and influencing factures among midwives in Ethiopia particularly the study area. Objective: To determine factors influencing midwives' professional belongingness in public hospitals in Amhara regional state, northwest Ethiopia, 2022. Methods: Institution-based cross-sectional study was conducted from February 21 to April 1, 2022. A cluster sampling technique was used to select 636 midwives. Data were collected using a self-administered and structured questionnaire, entered into Epi-Data version 4.6.software and exported to SPSS version 23 for analysis. A binary logistic regression analysis was fitted to identify factors associated with professional belongingness and p-value <0.05 at 95% confidence interval was used to declare statistical significance. Results: The proportion of belongingness was 52.7% (95% CI = 48.7, 56.6).Midwives who satisfied with their jobs [AOR = 3.50, CI= (2.48, 4.93)], had co-worker support [AOR = 1.54 CI= (1.08, 2.19)], had BEmONC training [AOR = 1.53 CI= (1.01, 2.30)], and experienced workplace violence [AOR = 0.55, CI= (0.39, 0.77)], had significant association with professional belongingness. Conclusion: The proportion of professional belongingness was low. Increasing job satisfaction, providing professional training, strengthening co-worker support, and developing workplace violence prevention strategies are all important steps toward increasing midwives' professional belongingness.